2002
DOI: 10.1037/0278-7393.28.6.1111
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the inhibitory account of retrieval-induced forgetting with implicit-memory tests.

Abstract: Five experiments examined whether retrieval-induced-forgetting effects are observed for implicit tests of memory. In each experiment participants first studied category-exemplar paired associates, then practiced retrieval for a subset of items from a subset of categories before finally completing memory tests for all the studied items. In standard fashion, inhibition was measured as the performance difference of unpracticed items from practiced categories and unpracticed items from unpracticed categories. Acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
82
4
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 13 publications
(36 reference statements)
5
82
4
1
Order By: Relevance
“…In recall tasks, some experiments report RIF effects with item-specific cues such as Fruit-Or_____ (e.g., M. C. Anderson & Bell, 2001; M. C. Anderson, E. L. Bjork, & R. A. Bjork, 2000;Bäuml, 2002;Bäuml & Hartinger, 2002), whereas others have failed to find them (Butler, Williams, Zacks, & Maki, 2001;Perfect, Moulin, Conway, & Perry, 2002). The evidence is similarly mixed in recognition tasks.…”
mentioning
confidence: 81%
“…In recall tasks, some experiments report RIF effects with item-specific cues such as Fruit-Or_____ (e.g., M. C. Anderson & Bell, 2001; M. C. Anderson, E. L. Bjork, & R. A. Bjork, 2000;Bäuml, 2002;Bäuml & Hartinger, 2002), whereas others have failed to find them (Butler, Williams, Zacks, & Maki, 2001;Perfect, Moulin, Conway, & Perry, 2002). The evidence is similarly mixed in recognition tasks.…”
mentioning
confidence: 81%
“…For healthy controls, recognizing previously-studied, weak associates may reflect both implicit and explicit mnemonic processes, the former influenced by familiarity and the latter by directed study and practice. Other studies of normal controls have also shown priming for implicit memory tests of recognition, instead of the RIF effect of worse performance for unpracticed items from practiced categories (Perfect et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Perfect et al (2002) found retrieval-induced forgetting with two implicit memory tests, but these tests did not employ independent cues. Instead, studied category cues were used.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the word-fragment completion task could not be regarded as truly implicit. Perfect, Moulin, Conway, and Perry (2002) used five different tests of implicit memory in the retrieval-practice paradigm: category generation, category verification, perceptual identification, category-cued perceptual identification, and word-stem completion. The retrieval-induced forgetting effect was found only with the category generation task and the category verification task.…”
mentioning
confidence: 99%